Resource-based View and Contingent Perspective on the Relationship between Geographic Diversification of Businesses and Organizational Performance - Aloisio Pereira Júnior; Vinícius Silva Pereira (BBR: Brazilian Business Review)
Recent meta-analyses have shown that the relationship between international diversification and performance can be moderated by the environment in which the company operates. According to the Contingency Theory, the performance of companies depends on the fit between the structure, processes and organizational environment. According to the Resource-Based View Theory, the way the company manages its resources contributes to its growth and guarantees of competitive advantage, and that resources can be accessed in the environment in which the company operates. Thus, the present work proposes a theoretical framework to analyze the effects of international diversification on the performance of companies based on the dynamism, complexity, and munificence of the companies’ operating environment, integrating the theoretical aspects of the Upstream-downstream Hypothesis, Contingency theory and RBV. This work contributes to the theory by proposing the theoretical aspects integration of different theories in the analysis of the relationship between international diversification and performance and allowing the outlining of opportunities for future research.